Numerical experiments on plasma focus pinch current limitation - Lee, S.; Lee, P.; Saw, S. H.; Rawat, R. S. (IOP Publishing, 2008)
Contrary to the general expectation that performance of a plasma focus would progressively improve with progressive reduction of its static inductance Lo, a recent paper suggests that there is in fact an optimum Lo below which although the peak total current increases progressively the pinch current and consequently the neutron yield of that plasma focuswould not increase, but instead decreases. This paper describes the numerical experiments and results that led to this conclusion.